Mindful parenting and subjective well-being in single mothers - Putrikita, Katrim Alifa; Hardika, Jelang; Rinaldi, Martaria Rizky (Universitas Sarjanawiyata Tamansiswa, 2024)
Single mothers have challenges in parenting because they have to care alone for their children, which affects their well-being. This research aims to examine the relationship between mindful parenting and subjective well-being among single mothers. The hypothesis in this study is that there is a positive correlation between mindful parenting and subjective well-being among single mothers. The subjects of this study are single mothers who have experienced divorce, either through a living or deceased spouse, within a range of one to five years. Data collection methods involve using the Mindfulness In Parenting Questionnaire (MIPQ) to assess mindful parenting and the Subjective Well-being scale. The data analysis method employed is the Pearson product-moment correlation. Based on the data analysis results, a correlation coefficient 0.553 is obtained with a significance level of p=0.000 (p < 0.050). These findings indicate a positive correlation between mindful parenting and subjective well-being, suggesting that higher levels of mindful parenting are associated with higher levels of subjective well-being among single mothers.